Novel C16orf57 mutations in patients with Poikiloderma with Neutropenia: bioinformatic analysis of the protein and predicted effects of all reported mutations - ELÇİOĞLU, HURİYE NURSEL (BIOMED CENTRAL LTD, 2012)
Background: Poikiloderma with Neutropenia (PN) is a rare autosomal recessive genodermatosis caused by C16orf57 mutations. To date 17 mutations have been identified in 31 PN patients. Results: We characterize six PN patients expanding the clinical phenotype of the syndrome and the mutational repertoire of the gene. We detect the two novel C16orf57 mutations, c.232C>T and c.265+2T>G, as well as the already reported c.179delC, c.531delA and c.693+1G>T mutations. cDNA analysis evidences the presence of aberrant transcripts, and bioinformatic prediction of C16orf57 protein structure gauges the mutations effects on the folded protein chain. Computational analysis of the C16orf57 protein shows two conserved H-X-S/T-X tetrapeptide motifs marking the active site of a two-fold pseudosymmetric structure recalling the 2H phosphoesterase superfamily. Based on this model C16orf57 is likely a 2H-active site enzyme functioning in RNA processing, as a presumptive RNA ligase. According to bioinformatic prediction, all known C16orf57 mutations, including the novel mutations herein described, impair the protein structure by either removing one or both tetrapeptide motifs or by destroying the symmetry of the native folding. Finally, we analyse the geographical distribution of the recurrent mutations that depicts clusters featuring a founder effect. Conclusions: In cohorts of patients clinically affected by genodermatoses with overlapping symptoms, the molecular screening of C16orf57 gene seems the proper way to address the correct diagnosis of PN, enabling the syndrome-specific oncosurveillance. The bioinformatic prediction of the C16orf57 protein structure denotes a very basic enzymatic function consistent with a housekeeping function. Detection of aberrant transcripts, also in cells from PN patients carrying early truncated mutations, suggests they might be translatable. Tissue-specific sensitivity to the lack of functionally correct protein accounts for the main cutaneous and haematological clinical signs of PN patients.
Keywords: Poikiloderma with Neutropenia; Dyskeratosis Congenita; Rothmund-Thomson; C16orf57; Founder effect; Bioinformatic prediction of C16orf57 protein; 2H phosphoesterase superfamily; RNA processing; Myelodysplasia; ROTHMUND-THOMSON-SYNDROME; CLERICUZIO-TYPE POIKILODERMA; DYSKERATOSIS-CONGENITA; MYELODYSPLASIA; GENERATION; FAMILY; GENE